Production of Bertholletia excelsa Humb. & Bonpl., (Lecythidaceae) seedlings in microenvironments under different substrates - Dionisio, Luiz Fernandes Silva (2019)
The lack of technological options for forest concessionaires to produce seedlings of native tree species in the Peruvian Amazon is a bottleneck for reforestation in the region. In this study, a new technology for seedlings production of low cost and accessible to producers was developed. Thus, the objective of this study was to evaluate the efficiency of using buckets as microenvironments under different substrates for the initial growth of Bertholletia excelsa seedlings. Forty days after germinating, the seedlings were transplanted to 115 cm³ tubes containing a standard substrate composed by sand + sawdust + charred sawdust in the proportion of 1:1:1 v/v. Afterwards, the tubes were settled in buckets (microenvironments) under a 100% shade net. The experimental design used in this study was fully randomized and the treatments were T1 = sand, T2 = sand + sawdust, T3 = decomposed Brazil nut shell and T4 = forest soil. The substrate T2 promoted the shoot length, root length, leaves number, shoot dry mass, root dry mass, total dry mass, and slenderness index in B. excelsa seedlings. Quality of B. excelsa seedlings produced in microenvironments was similar among treatments, regardless of the used substrate.